Konsep Kesejahteraan Sosial Menurut Masyarakat Melayu Di Batubara - Chairun Nisa; Yakobus Ndoda (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to explore the concept of social welfare according to the Malay community in Batu Bara, North Sumatra, in the context of the fifth principle of Pancasila values: